2018
DOI: 10.1093/mnras/sty2841
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent oscillation modes in rotating superfluid neutron stars

Abstract: We calculate the spectrum of inertial oscillation modes in a slowly rotating superfluid neutron star, including, for the first time, both the effects of finite temperatures and entrainment between superfluid neutrons and protons. We work in the Newtonian limit and assume minimal core composition (neutrons, protons and electrons). We also developed an approximate method that allows one to calculate the superfluid r-mode analytically. Finally, we derive and analyze dispersion relations for inertial modes in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…We have found that in thermodynamic equilibrium the quasi-particle current is locked to the entropy current, or, in other words, the entropy is transported by the excitations, in agreement with the Landau theory of superfluidity [40], see equations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and of Khalatnikov [31]. The two equilibrium conditions (59) and (60) are also in accordance with the derivation of the thermodynamics of a generic multifluid presented in [10].…”
Section: A Equilibration Dynamics and Equilibrium Conditionssupporting
confidence: 74%
See 1 more Smart Citation
“…We have found that in thermodynamic equilibrium the quasi-particle current is locked to the entropy current, or, in other words, the entropy is transported by the excitations, in agreement with the Landau theory of superfluidity [40], see equations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and of Khalatnikov [31]. The two equilibrium conditions (59) and (60) are also in accordance with the derivation of the thermodynamics of a generic multifluid presented in [10].…”
Section: A Equilibration Dynamics and Equilibrium Conditionssupporting
confidence: 74%
“…In the absence of dissipation, it has been shown [10] that the phenomenological multifluid of Carter and Khalatnikov is an exact reformulation of the more fundamental models for a relativistic superfluid of Son [11] and Gusakov [12]. Moreover, Carter's multifluid is a convenient formalism to describe neutron stars [13,14], notably their structure [15,16], oscillations [17][18][19] and the phenomenon of pulsar glitches [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Although observed neutron stars are usually cold, meaning that their internal temperature T is much lower than the Fermi temperatures T Fq , thermal effects may still be significant for the superfluid dynamics since the associated critical temperatures T cq are typically much lower than T Fq . In particular, it has been recently shown that the temperature dependence of the entrainment matrix may have implications for neutron-star oscillations [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…To put it on a solid ground and to prove that the avoided-crossings of the most unstable r-mode with SF modes take place in the parameter range relevant to NSs in LMXBs, one has to calculate the r-mode spectrum for SF NSs at finite temperatures. This goal had been reached in the previous studies [18,19] under certain assumptions. Namely, Ref.…”
Section: Introductionmentioning
confidence: 95%
“…[18] calculated the r-mode spectrum for a SF neutron star stratified by muons, neglecting the entrainment between neutrons and protons (i.e., assuming that motion of one particle species does not induce particle current of another species). Subsequent work [19] accounted for the entrainment effect, but assumed that NS core consists of neutrons, protons, and electrons only. Here we calculate the spectrum allowing for both muons and entrainment in the core, and show that together they change the spectrum qualitatively.…”
Section: Introductionmentioning
confidence: 99%